2016
DOI: 10.15625/0866-7187/37/3/7799
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aerosol optical depth retrieved from AERONET in Vietnam and comparison with MODIS data

Abstract: Đặc điểm độ dày quang học sol khí từ số liệu các trạm AERONET Mở đầu Sol khí (aerosol) bao gồm các hạt rắn, lỏng tồn tại lơ lửng trong khí quyển, là một trong những tác nhân quan trọng gây nên biến đổi tính chất quang học, hóa học khí quyển, chúng tác động tới quá trình hình thành mây, tán xạ và hấp thụ năng lượng  Tác giả liên hệ, Email: pxthanh@igp-vast.vn bức xạ, gây nên những biến đổi trong hệ thống thời tiết -khí hậu. Các phần tử sol khí tán xạ và hấp thụ bức xạ làm cho lớp khí quyển ấm lên và bề mặ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…In addition, the measured AODs of both MODIS and AERONET in June are another high peak (0.973 and 0.975) with large standard deviation values (0.772 and 0.881). Pham et al [12] also reported similar findings that AOD load at Nghia Do station were high during the beginning of winter months (October and November), and during the late winter months (March and April). Tran et al [19] also found that AOD load in Hanoi were high in October and March because of monsoon circulation affection and biomass burning.…”
Section: Methods For Comparison Between Modis Satellite-based and Aerosupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the measured AODs of both MODIS and AERONET in June are another high peak (0.973 and 0.975) with large standard deviation values (0.772 and 0.881). Pham et al [12] also reported similar findings that AOD load at Nghia Do station were high during the beginning of winter months (October and November), and during the late winter months (March and April). Tran et al [19] also found that AOD load in Hanoi were high in October and March because of monsoon circulation affection and biomass burning.…”
Section: Methods For Comparison Between Modis Satellite-based and Aerosupporting
confidence: 56%
“…However, according to our intensive literature review, there have been few studies conducted in Vietnam relating to MODIS AOD satellite data so far. To our knowledge, there are only two researches that compare MODIS AOD and ground-based AERONET AOD measurements [12]. However, these researches used MODIS AOD Collection 5 product.…”
Section: Introductionmentioning
confidence: 99%
“…GIS tools are utilized to evaluate the relationships between factors causing landslides and to make a map of landslide susceptibility or risk for landslides. Recent studies showed the importance of determining weighted factors of landslide risk by the analytical hierarchy process (AHP) approach, which was mainly based on the intention of the experts (Minh et al 2011;Tuan and Nguyen 2012;Tham, Do, and Kanh 2012). Therefore, this study was conducted based on a statistical analysis of landslide risk and results of interviews with local people living in a landslide-prone region, to ensure objectivity in identifying the factors causing landslides.…”
mentioning
confidence: 99%